Improvement of Atopic Dermatitis Severity after Reducing Indoor Air Pollutants - Kim, Hye One (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2013)
BACKGROUND: Recent epidemiologic studies have shown that environmental contaminants such as air pollution and tobacco smoke play an important role in the pathophysiology of atopic dermatitis (AD). OBJECTIVE: The aim of this study was to evaluate the relationship between the severity of AD and indoor air pollution. METHODS: The study population consisted of 425 children from 9 kindergartens, Korea. The authors surveyed the prevalence of AD and evaluated disease severity by the eczema area and severity index (EASI) score and investigator's global assessment (IGA). After measuring indoor air pollution, a program to improve indoor air quality was conducted in 9 kindergartens. Seven months later, the prevalence and disease severity were evaluated. RESULTS: The initial prevalence of AD was 8% and the mean EASI score was 2.37. The levels of particulate material 10 (PM(10)) and carbon dioxide (CO(2)) were higher in some kindergartens compared to the normal values. Subsequent to the completion of the indoor air quality improvement program, the mean PM(10) level was significantly decreased from 182.7 to 73.4 µg/m(3). After the completion of the program, the prevalence of AD and the mean EASI were decreased, and the changes were both statistically significant. The mean number of hospital visits decreased from 1.3 per month during the first survey to 0.7 per month during the second survey, which was statistically significant. CONCLUSION: Indoor air pollution could be related to AD. The reduction of PM(10) through improving indoor air quality should be considered in kindergartens and schools in order to prevent and relieve AD in children.